PERANCANGAN KOMUNIKASI VISUAL PROMOSI WISATA KABUPATEN SOLOK DALAM MEDIA BOOKLET - Yovan Marta, Drs. Irwan, M.Sn, Hendra Afriwan, S.Sn, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
The county of Solok which is recognized as “Solok nan Indah” has many interesting tourism objects such as culture, nature, religion and others but most of tourist both of local and oversea do not realize it. Promotion is very needed to make the county of Solok is known by tourist. This article explains about using booklet as a visual media to promote tourism object in the county. Besides that, it also states other media to support booklet in promoting tourism in the county. They are billboard, calendar, brochure, sticker, poster, and CD. The methods that are used in creating a booklet are SWOT (strength, weakness, opportunity, threat), AIDAS (Attention, Interest, Desire, Action, Satisfaction) and USP(unique selling positioning). All of the media have purpose to develop tourism in county of Solok so it will be known by tourist. Applying booklet can add kinds of media to promote tourism object of the county of Solok. Key words: Tourism, Promotion, Booklet